Penerapan Metode AHP dan Metode TOPSIS Dalam Menentukan Asisten Laboratorium Komputer - Farih, Nia Nailil; Hadikurniawati, Wiwien (STIKOM Tunas Bangsa Pematangsiantar, 2023)
The process of developing a decision support system for accepting computer laboratory assistants uses the Analytical Hierarchy Process (AHP) and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) methods. for the criteria weighting process and the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method for the alternative ranking process. The results of the weighting of the criteria that have been calculated, the TOPSIS method is used for the alternative ranking process.